Prevalence, incidence and risk factors for rugby-related injuries: A survey of the Safari Sevens tournament - John M. Onyancha; Olivier Benita; Joseph M. Matheri; Wallace M. Karuguti (AOSIS, 2024)
Background: Rugby-related injuries are a leading cause of dropout from competitive sports, high insurance compensation, disability and socioeconomic marginalisation. The debilitating effect of these injuries on players may deny them the benefits associated with rugby and can lead to premature termination of a rugby career. Objectives: To determine the prevalence, incidence and risk factors for rugby-related injuries among male Safari Sevens rugby tournament players in Kenya. Method: Following ethical approval and clearance, this cross-sectional study was carried out among October 2021 teams of male players in the Safari Sevens rugby tournament. Players (n = 113) voluntarily completed Rugby International Consensus Group 'injury report form'. Descriptive statistics and odds ratios were calculated. Results: A point prevalence of 47 (41.6%) respondents at pre-tournament was found. The tournament recorded 117.6 player-match hours with an incidence of 33 (29.2%) injuries occurring during competition. In contact phase of rugby match, 'being tackled' was associated with a higher number of injuries mostly in the lower limbs. Surface of the playing field was likely to expose a player to injury in pre-competition and during the tournament. Additionally, players who had recurrent previous injuries and oversize gear were more likely to be injured during the tournament. Conclusion: The study showed competition injury incidence similar to that reported in previous studies. Lower limb injuries were most prevalent, especially the ankle while 'getting tackled' during matches. Clinical implications: There is a need for an algorithm for injury risk assessment, knee and ankle control training protocol, and use of dynamic knee and ankle supports.